MANAJEMEN REKRUTMEN TENAGA PENDIDIK (GURU) - Putriyani (CV. Amerta Media, 2018)
The success of teacher recruitment is a beginning of the education institutions to have the good quality performance. There are several procedures that must be considered in the implementation of teacher recruitment to get employees who required as the positions. This paper explains the concept of teacher recruitment management. The focus of this paper will explain the teacher recruitment management deeply to find out how the principles of recruitment, recruitment planning, recruitment process and the selection process of the teachers as required in the education institutions.Key Word: Management, recruitment, teacher